High Reliable Relay Selection Approach for QoS Provisioning in Wireless Distributed Sensor Networks - Yong Jin (International Journal of Distributed Sensor Networks)
In wireless distributed sensor networks, one open problem is how to guarantee the reliable relay selection based on the quality of services diversity. To address this problem, we focus on the reliable adaptive relay selection approach and adaptive QoS supported algorithm, based on which we present a Markov chain model, in consideration of different packet states and error control algorithm assignment. The mathematical analyses and NS-2 simulation results show that the proposed relay selection approach could perform better in terms of saturation throughput, reliability, and energy efficiency, compared with the traditional approaches. More importantly, the quality of real-time multimedia streaming is improved significantly, in terms of decodable frame ratio and delay.